Taxonomic notes on the genus Elaphromyia Bigot (Diptera: Tephritidae: Tephritinae: Pliomelaenini) in India, with description of a new species - David, K.j.; Hancock, D.l.; Sachin, K.; Ramya, R.s.; Ramani, S. (Zootaxa, 2021)
A new species of Elaphromyia, E. juncta David, Hancock & Sachin, sp. n. is described from India. It can be differentiated from the morphologically similar E. siva Frey and E. pterocallaeformis (Bezzi) by the wing pattern, epandrial characters, morphology of spicules on the eversible membrane and spermathecal shape. Elaphromyia siva Frey and E. yunnanensis Wang are recorded for the first time from India. Records of E. pterocallaeformis (Bezzi) from southern India are regarded as misidentifications. A key to the 7 known non-African species is included.